2014
DOI: 10.1128/jb.01293-13
|View full text |Cite
|
Sign up to set email alerts
|

Natural Competence and the Evolution of DNA Uptake Specificity

Abstract: Many bacteria are naturally competent, able to actively transport environmental DNA fragments across their cell envelope and into their cytoplasm. Because incoming DNA fragments can recombine with and replace homologous segments of the chromosome, competence provides cells with a potent mechanism of horizontal gene transfer as well as access to the nutrients in extracellular DNA. This review starts with an introductory overview of competence and continues with a detailed consideration of the DNA uptake specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
194
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(199 citation statements)
references
References 131 publications
2
194
1
2
Order By: Relevance
“…However, transformation efficiency was shown to be very low for strain CIP 70.10 (49). Moreover, DNA uptake of fragments Ͼ50 kb by natural transformation currently has to be considered a great challenge for the cell (50), and nucleases may restrict incoming DNA (51).…”
Section: Figmentioning
confidence: 99%
“…However, transformation efficiency was shown to be very low for strain CIP 70.10 (49). Moreover, DNA uptake of fragments Ͼ50 kb by natural transformation currently has to be considered a great challenge for the cell (50), and nucleases may restrict incoming DNA (51).…”
Section: Figmentioning
confidence: 99%
“…Collectively, these observations suggested to us that the ComE pore might be involved in the release of DNA and DNABII proteins from the periplasmic space into the extracellular environment, given that the secretin pore is just wide enough to accommodate a pair of DNA double helices (51). Therefore, we constructed an isogenic comE mutant and found that NTHI that could not express the ComE pore did not release DNA via the mechanism observed with the parent strain.…”
Section: Discussionmentioning
confidence: 99%
“…NTHI expresses Tfp from a single subpolar location along the long axis of the bacterial cell. These Tfp are essential for twitching motility, adherence to respiratory tract epithelial cells, colonization of the mammalian respiratory tract, and competence (10,44,45,50,51). The Tfp machinery in NTHI is encoded by two operons, pilABCD and comABCDEF.…”
Section: Discussionmentioning
confidence: 99%
“…Two DUS variants, distinguished by two bases immediately preceding the 10-mer, are abundant in neisserial genomes: 5¢-agGCCGTCTGAA-3¢ and 5¢-atGCCG TCTGAA-3¢. agDUS is most abundant in human commensals N. elongata, N. bacilliformis and Neisseria subflava, and the dog commensal N. weaveri (Frye et al, 2013;Mell & Redfield, 2014), while atDUS is most abundant in human commensals Neisseria cinerea, Neisseria lactamica and Neisseria polysaccharea, and the human pathogens N. gonorrhoeae and N. meningitidis.…”
Section: A Detailed Analysis Of Ap2031mentioning
confidence: 99%